Relevansi Moral dan Karakter Siswa Sekolah Dasar Ditinjau dari Aspek Kehidupan Sosial - Azmi Sekar Putri; Fatimah Azzahra; Hilda Rahmah; Lusi Tri Anggraeni (Universitas Batanghari Jambi, 2023)
Today, the relevance of morality and character of primary school children has a significant influence on their social development. Therefore, the purpose of this study is to develop moral principles and good character in children, one of which is through character education. The research method used is descriptive research. The results showed that character education is a process of forming children's personalities to develop into good citizens and be able to recognize signs of moral crisis and play a role in the framework of coaching the younger generation. This is closely related to the support provided by the school environment, which includes an appropriate physical environment, a social environment that encourages cooperation between students, teachers, and staff, as well as an academic environment that encourages superior behavior from students.